Thermal activation of basic oxygen furnace slag as a heterogeneous catalyst in transesterification: Characterization and catalytic activity studies - J.S. Ali; H.L. Rutto; T. Seodigeng; S.L. Kiambi (Results in Engineering)
The valorization of industrial by-products has garnered significant attention in recent years due to its potential to enhance sustainability and economic efficiency within various sectors. Basic Oxygen Furnace slag (BOF-S), a by-product generated in the steelmaking process characterized by its complex composition, presents an opportunity for waste management and resource recovery. This study investigates the potential of BOF-S as a catalyst in converting waste cooking oil to biodiesel via the transesterification reaction. To improve its efficiency, BOF-S was calcined at 850 °C (BOF-S 850), and 1000 °C (BOF-S 1000), for 5 h. The BOF-S was characterized using XRF, N2 sorption, XRD, TGA-DSC, SEM-EDS and FTIR. The characterization techniques showed that the BOF-S 850 had superior characteristics as a catalyst: rough surface, increased pore size and more active basic sites compared to the BOF-S and the BOF-S 1000 slag samples. The transesterification reaction was conducted at a methanol: oil ratio of 20:1, a catalyst loading of 20 wt %, a reaction time of 12 h, a reaction temperature of 60 °C, and a stirring speed of 750 rpm. The findings established that the BOF-S 850 was the best catalyst, with a 90.77 % biodiesel yield and was able to sustain a maximum of two transesterification cycle runs.